HealthKick : evaluating the impact of a school-based intervention on the dietary adequacy of learners from low-income settings in the Western Cape Province, South Africa - Abrahams, Zulfa (Department of Public Health and Family Medicine, 2014)
HealthKick is a primary school-based nutrition and physical activity intervention programme aimed at promoting the adoption of healthy lifestyle behaviour to reduce diabetes risk factors in disadvantaged communities in South Africa. HealthKick aims to promote and increase learners', teachers' and parents' consumption of healthy food and their participation in health enhancing physical activity. This dissertation sub-study forms part of the evaluation of the greater HealthKick project. The primary objective of the study was to compare the dietary adequacy of learners at intervention and control schools after 18 months of intervention. The subsidiary objective was to identify the determinants of dietary adequacy.